Technical Efficiency of Dairy Farms in Central Kosovo - Shkodra, Reuf; János, Felföldi; Kovács, Krisztián; Maloku, Donika (International Journal of Economics and Financial Issues, 2020)
Kosovo has the key resources needed for a developed agriculture. However, Kosovo's agriculture consists of very small farms which are featured with the fragmentation of their land, old buildings and equipment, though functional. Ministry of Agriculture (MAFRD) started to support farmers with direct payments in 2009, but only for a few agricultural cultures. Support for dairy cows started in 2012, and support for milk quality started in 2014. In this context, the purpose of this paper is to accurately portray the characteristics, and technical efficiency of dairy farms in Central Kosovo, respectively in the region of Pristina - beneficiaries of direct payments for milk quality. Consequently, through Data Envelopment Analysis (DEA), under Variable Return to Scale (VRS) using output orientation, the efficiency rate of dairy farmers is calculated. Therefore, findings show that not all the farms are fully efficient, or fully utilizing their assets and their inputs. Additionally, the study revealed that the size of the farm, and the feeding system affect the TE. Therefore, large-size farms and farms who used seasonal grazing had overall higher TE. However, the level of education does not have a significant effect on the farm's efficiency. Keywords: Dairy sector, Kosovo, Technical Efficiency, Data envelopment analysis JEL Classifications: D24, Q12, Q1 DOI: https://doi.org/10.32479/ijefi.9630